PERSONALITY-ORIENTED APPROACH USING IN PROFESSIONAL TRAINING OF THE FUTURE MUSIC ART TEACHERS TO VOCAL PEDAGOGICAL ACTIVITY - Ovcharenko, Nataliia (Continuing Professional Education: Theory and Practice, 2019)
The problem of personality-oriented approach using in professional training of the future music art teachers to vocal pedagogical activity is explored in this article. There are such specific threats as capture maintenance of professional training of students on the individual lessons from voice training; necessity of the vocal natural skills of students; unevenness of the vocal preparation and vocal natural skills of students; an exceptional role of auditory presentations of teacher is from the voice training about the standard of sound; combination in vocal music of poetic and musical types of art; vocal repertoire which is oriented to every student separately. Due to analysis of scientific-theoretical experience of problem in personality-oriented education of the future music art teachers were separated prospects of such training. Introduction of the personality oriented educational plan is offered and portfolio vocally pedagogical achievements of students. Application of them will be instrumental in growth of future specialist not only as a performer but also as a teacher, Methodist, enlightener, organizer, researcher, and others like that. Personality-oriented educated plan provides for growth of the future teacher on music not only as a performer but as a teacher, enlightener, organizer, researcher etc. Implementation of the personality – oriented plan is fixed in portfolio. There are vocal-pedagogical achievements of student such as:a letter of educational results, video recordings of competitive and concerto appearances, vocal-methodological and performing activity on the summer practice, photos, diplomas, deeds, methodological reports and articles.